2007
DOI: 10.1016/j.bone.2006.09.029
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation at the low-density lipoprotein receptor-related protein 5 (LRP5) locus modulates Wnt signaling and the relationship of physical activity with bone mineral density in men

Abstract: Polymorphisms in the LRP5 gene have been associated with bone mineral density (BMD) in men and/or women. However, the functional basis for this association remains obscure. We hypothesized that LRP5 alleles could modulate Wnt signaling and the relationship between physical activity and BMD.This genetic association study was performed in the population-based Framingham Study Offspring Cohort, and included a subset of 1797 unrelated individuals who provided blood samples for DNA and who had BMD measurements of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
81
3
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(97 citation statements)
references
References 55 publications
10
81
3
3
Order By: Relevance
“…In human studies, the association between polymorphisms in Lrp5 and BMD have been found to be modified by exercise. (28,29) Thus, the larger tibial but not radial perimeter observed in LRP5-HBM individuals corroborates the association between Wnt signaling and skeletal responses to mechanical strain and exercise. Contrary to previous studies showing increased (2) or comparable levels of OC in Lrp5-HBM patients, (15) OC was lower in cases than controls in our study.…”
Section: Discussionsupporting
confidence: 59%
“…In human studies, the association between polymorphisms in Lrp5 and BMD have been found to be modified by exercise. (28,29) Thus, the larger tibial but not radial perimeter observed in LRP5-HBM individuals corroborates the association between Wnt signaling and skeletal responses to mechanical strain and exercise. Contrary to previous studies showing increased (2) or comparable levels of OC in Lrp5-HBM patients, (15) OC was lower in cases than controls in our study.…”
Section: Discussionsupporting
confidence: 59%
“…(61) Additionally, in a large human genetic association study, several single-nucleotide polymorphisms (SNPs) were found in LRP5 that significantly affected the relationship between physical activity and bone mineral density, further supporting a function for LRP5 in mechanotransduction. (62) Taken together, these data indicate that LRP5 plays a key role in translating mechanical signaling into the proper skeletal response.…”
Section: Osteocytes Mechanical Loading and Interface With The Pth Pmentioning
confidence: 76%
“…These results complement in vivo studies in animals (24) and human subjects (6), which show increases in bone formation after treatment with strontium ranelate. Because stimulation of the canonical Wnt pathway is also osteogenic in vivo (25) we investigated whether strontium ranelate affected canonical Wnt signaling in primary human osteoblasts.…”
mentioning
confidence: 99%